Phytochemical Characterization and Antiplatelet Activity of Mexican Red Wines and Their By-products - Muñoz-Bernal, Ó.A.; de la Rosa, L.A.; Rodrigo-García, J.; Martínez-Ruiz, N.R.; Sáyago-Ayerdi, S.; Rodriguez, L.; Fuentes, E.; Alvarez-Parrilla, E. (South African Journal of Enology and Viticulture, 2021)
Red wines and their grape pomaces are important sources of phenolic compounds. Inhibition of platelet aggregation is one of the mechanisms proposed for cardioprotective effect of phenolic compounds from wine and grape pomace; however, phenolic content is affected by region, variety and winemaking process. In the present study, antiplatelet effect of red wines and grape pomaces was related to its phenolic content (determined by spectrophotometric techniques) and profile (determined using HPLC-MS/MS). in vitro Anti-platelet aggregation was determined using human platelets. Results showed that Zinfandel wine and Cabernet Sauvignon grape pomace presented the highest phenolic content. Phenolic profiles presented differences in the presence of flavonoids and oligomeric tannins. Results from platelet aggregation showed that Merlot and Petit Verdot wines and Petit Verdot grape pomace sample presented the highest antiaggregant effect. These results indicate that antiplatelet effect could be related to phenolic profile than phenolic content in wines and grape pomaces. Cardioprotective effect of red wines and grape pomace could be related to specific compounds such as monomeric and polymeric flavan-3-ols.